Resistance to CLnA-induced ferroptosis is acquired in Caco-2 cells upon differentiation - Cuvelier, Géraldine; Vermonden, Perrine; Rousseau, Justine; Feron, Olivier; Rezsohazy, René; Larondelle, Yvan (Frontiers in Cell Death, 2023)
In contrast to canonical ferroptosis inducers, highly peroxidable conjugated linolenic acids (CLnA) directly fuel the lipid peroxidation cascade upon their incorporation into membrane phospholipids. Little is known, however, about the cytotoxicity level of CLnAs to normal epithelial cells. Caco-2 cells, derived from colorectal adenocarcinoma, spontaneously differentiate into enterocyte-like cells over a period of 21 days of cell culturing, allowing for graduated phenotypic shift from proliferative, undifferentiated cells to a functional intestinal barrier. We exploited this property to assess the sensitivity of Caco-2 cells to CLnAs at different stages of differentiation. Our results show a significant decrease in CLnA-induced ferroptotic cell death over time. The acquired resistance aligned with decreases in cell proliferation and in the extent of lipid peroxidation, as well as with an increase in the expression of GPX4 upon differentiation. These results highlight that while CLnAs are highly toxic for proliferating cancer cells, differentiated epithelial cells are resistant to CLnA-induced ferroptosis. Therefore, this study gives credential to the therapeutic use of CLnAs as an anticancer strategy and offers a new model study to further investigate the safety of peroxidable fatty acids in differentiated cells.